Root Distribution, Agronomic Performance, and Phosphorus Utilization in Wheat as Mediated by Phosphorus Placement under Rainfed Coastal Saline Conditions - De-Yong Zhao; Xiao-Lin Zhang; Wang-Feng Zhao; Shuai-Peng Zhao; Guo-Lan Liu; Kadambot H. M. Siddique (Agronomy, 2023)
Rainfall variations between seasons could affect phosphorus translocation from rainfed saline soil to wheat plants. Whether deep-banded P application increases wheat yield compared to traditional P placement under rainfed coastal saline conditions remains a question. This study investigated the impact of season, P placement, and genotype on root distribution, agronomic performance, and P utilization in wheat grown under rainfed coastal saline conditions. Four wheat genotypes (two tall genotypes (Alice and Shavano) and two dwarf genotypes (AK58 and LX99)) were grown in a saline field with five P placement treatments (Top-dressed High P input (TopHP), Deep-banded High P input (DeepHP), Top-dressed Reduced P input (TopRP), Deep-banded Reduced P input (DeepRP), and no P supply (No P)) for two consecutive seasons. Root length density (RLD), agronomic traits, nutrient concentrations in grain and straw, and P utilization efficiency were determined. Statistical analysis was employed to compare the P utilization across treatments. TopHP increased RLD at a 0–20 cm depth, while deep-banded P increased RLD at a 20–40 cm depth. The wet season (2021–2022) resulted in higher grain yields, more fertile spikelets, and fewer non-fertile spikelets in all four genotypes than the dry season (2020–2021). The highest 1000-kernel weights occurred in DeepHP or TopHP. Deep-banded P outperformed top-dressed P placement in terms of P utilization efficiency for LX99, Shavano, and AK58 (not Alice) in both seasons. Nutrient concentrations/accumulations showed inconsistent patterns due to significant genotype × P placement interactions. PCA analysis revealed that first two PCs accounted for 56.19% and 60.13% of the variance in the 2020–2021 and 2021–2022 seasons, respectively. The first component (PC1) represented root spatial distribution and straw weight, while the second component (PC2) represented 1000-kernel weight, grain number per head, and grain yield. Altered P utilization efficiency mediated by P placement was associated with changes in wheat root distribution, agronomic traits, and nutrient concentrations in straw and grain. The increased wheat yield in the wet season (2021–2022) was attributed to higher rainfall.